Comparison of Morphological Characters of Freshwater Crayfish (Cherax quadricarinatus) from Different Ecosystems in Indonesia - Bambang Widigdo; Agus Alim Hakim; Ali Mashar; Iya Purnama Sari; Yusli Wardiatno (Jurnal Biologi Tropis, 2020)
Freshwater crayfish (Cherax quadricarinatus) as an invasive species has high capability to adapt in most waters in Indonesia. The extant distribution of this species in Indonesia causes observation of morphological charactersÃÂ  is important to be established. This study purpose is to compare the morphological characters of Cherax quadricarinatus from several locations in Indonesia waters, such as the river in Bintan Island, Toba Lake, and Lido Lake. The total of morphological characters was measured in twenty-two characters. The result of the Kruskal-Wallis test represented nine different characters between Toba, Bintan, and Lido. Cluster analysis illustrated the highest level of similarities between Toba and Lido. The growth rate of the dactyls, and carapace width, and ocular carapace length between Toba and Lido were similar, meanwhile between Toba and Bintan were different. C. quadricarinatus originating from river waters in Bintan Island has a different morphological character from Lake Lido and Lake Toba. The differences in morphological characters between locations are caused by differences in habitat characteristics in rivers and lakes.